Confined Pyrolysis of ZIF‐8 Polyhedrons Wrapped with Graphene Oxide Nanosheets to Prepare 3D Porous Carbon Heterostructures. Issue 11 (24th June 2019) - Ding, Bing; Fan, Zengjie; Lin, Qingyang; Wang, Jie; Chang, Zhi; Li, Tao; Henzie, Joel; Kim, Jeonghun; Dou, Hui; Zhang, Xiaogang; Yamauchi, Yusuke
Abstract: Heterostructured materials are interesting because they may combine two or more material building blocks that together generate new types of heterointerfaces with unusual properties. Using them to construct large‐scale 3D frameworks further extends their utility in electrochemical applications because it exposes more interfaces and active sites. In this study, electrostatic interactions are used to wrap polyhedra particles of zeolitic imidazolate frameworks with graphene oxide (GO) nanosheets to prepare the composite structure. Pyrolyzing this structure generates a 3D porous carbon framework (PCF) composed of polyhedral‐shaped hollow carbon coated with reduced GO. The size of the polyhedral macropores can be adjusted from nanometer scale to micrometer scale. The PCFs generate a continuous network of heterostructured carbon with a large surface area and large pore volumes that are particularly useful as porous electrodes in lithium–sulfur batteries. The PCF/S composite electrode exhibits a high discharge capacity of 1151 mAh g −1 at 1 C and a low capacity decay of 0.035% per cycle after 650 cycles. Abstract : 3D porous carbon framework (PCF), composed of polyhedral‐shaped hollow carbon coated with graphene nanosheets, is prepared through electrostatic interaction‐driven self‐assembly followed by confined‐space pyrolysis. When used as a host material for lithium−sulfur batteries, the PCF/S electrode exhibits a high capacity and a low capacity decay of 0.035% per cycle after 650 cycles at 1 C.